Environmental conflicts in protection forest mostly caused by issues of scarcity, negative externalities, structural unbalance, and different viewpoint of people on value of forests. In many cases, forest governance creates overlapping policies regarding with these issues that may generate conflict escalation; this occurs in Register 45B of Protection Forest Zone in Lampung Province. This research aimed to study (1) factors those affecting (escalation of) conflict, (2) conflict management style - Gamal Pasya; Kooswardhono Mudikdjo; Sediono M.P. Tjondronegoro; Cecep Kusmana; Siti Nurbaya (Forum Pasca Sarjana, 2011)
Environmental conflicts in protection forest mostly caused by issues of scarcity, negative externalities, structural unbalance, and different viewpoint of people on value of forests. In many cases, forest governance creates overlapping policies regarding with these issues that may generate conflict escalation; this occurs in Register 45B of Protection Forest Zone in Lampung Province. This research aimed to study (1) factors those affecting (escalation of) conflict, (2) conflict management styles manifested by parties/disputants, (3) polarization of parties refer to the conflict roots they face, and (4) settlement options that parties willing to take referring to alternative dispute resolution (ADR) options. Research implementation and analysis carried out by using pathway analysis and pairwise comparison analysis-scheffe test. The research found that conflict escalation was mainly caused by decision to convert forest land use. Conflict management styles are collaborative and compromise. Polarizations of parties refer to similarities on interests. All parties willing to take negotiation and/or facilitation as ADR options to settle disputes. Key words: conflict, environment, forest, resolution